Mengungkap Kekayaan Etnobotani: Pemanfaatan Tumbuhan Obat dalam Jamu Legendaris di Kampung Jamu Kromengan Kabupaten Malang - Celena Qonitah; Mochamad Ringga Febriansyah; Natasya Aurellya Putri; Fahrul Ghani Muhaimin; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
Traditional knowledge regarding the utilization of medicinal plants as ingredients for traditional herbal medicine (jamu) in Karangrejo Village, Kampung Jamu Kromengan, represents a form of local wisdom that is still maintained by the community. This study aimed to identify the diversity of medicinal plants and analyze their utilization levels based on quantitative ethnobotanical indices. The research employed a mixed-method approach with an exploratory sequential design through interviews, observations, documentation, and questionnaire surveys. The results revealed 12 species of medicinal plants belonging to 6 families, with the Zingiberaceae family dominating (7 species). Rhizomes were the most frequently utilized plant part, with a PPUV value of 48.8%, indicating the community’s high reliance on rhizomatous plants in jamu preparation. The highest ICF value (0.97) in the categories of relieving muscle aches and increasing appetite indicated a strong level of community agreement regarding the use of certain plants for these health conditions. The highest RFC values were found in kencur and rice, the highest SUV in turmeric, the highest FUV in the Zingiberaceae family, and the highest FL in temulawak for increasing appetite, indicating that plants from the Zingiberaceae family have high utilization, trust, and ethnobotanical importance in traditional jamu practices. In conclusion, jamu practices in Karangrejo Village are dominated by the use of rhizomatous plants, which play an important role in traditional medicine and reflect the strong local knowledge of the community regarding the use of medicinal plants.